PERLINDUNGAN HUKUM TERHADAP PARA PIHAK DALAM PERJANJIAN PENGIKATAN JUAL BELI TANAH YANG DIBUAT DIBAWAH TANGAN OLEH PT.CISADANE PERDANA DI KOTA DEPOK - Dyah Ayu Silviana, Endang Sri Santi*), Triyono (Diponegoro Law Journal, 2013)
Land and Housing is a basic human need that has a very important role in people's lives. Housing needs of people today as well as the need for food and shelter. On the other hand  economic  development   and  residential  land  development  business  is  also experiencing rapid growth. Among these legal actions is the act of housing ownership laws regarding the sale and purchase. The sale and purchase of the housing is selling house and land is not always carried out with cash and cash. So much for the housing developer company then used the letter standard Sale and Purchase Agreement as a sale purchase agreement, which is not made before the General Officer (Notary). Although it was set on buying and selling land, but the format is merely a binding sale and purchase agreement is a form that can be said as penduhuluan agreement. So a situation like this would  be  a  problem  how  much  evidence  and  legal  certainty  of  binding  sale  and purchase agreement made under the hand. In other research will be discussed in the power of the law of treaties binding sale and purchase of land made under the hand, especially when made by PT Cisadane Prime in Depok and legal protection of  the  parties to the purchase agreement made under the hand. The study is a descriptive analysis with empirical juridical approach, whereas the data obtained through library research and field research based on the subject and object of research. Furthermore, the data were analyzed qualitatively. From the results of this study concluded that the legal force of treaties binding sale deed of land made under the hand, especially when made by PT Cisadane Prime in Depok to the customer is to have the same legal force to the deed of Sale and Purchase agreement (SPA) created under the arms, the strength based on the Civil Code Article 1338 Civil Code, which reads: all agreements made legally valid as a law for those who make it and the legal protection of the fulfillment of the rights of the parties where one party in default under binding purchase agreement is dependent upon the strength of binding sale and purchase agreement made, that if made by deed under the hand of protection in accordance with the  protection of the deed under hand. Meanwhile, when made by a notary or the deed itself aktanya be notaril that force protection in accordance with the protection of an authentic deed.